Developing a Toolkit to Support Dissemination and Implementation of the Red Carpet Entry Program. - Holt, Sidney L.; Ortiz, Alexa; Rivell, Aileen; Vu, Kathy L.; Mullen, Nicole; Jordan, Alyssa; Galindo, Carla A.; Betts, Joshua E.; Gelaude, Deborah (AIDS & Behavior, 2026)
The Red Carpet Entry (RCE) program is an evidence-informed structural intervention to improve linkage to HIV care within 72 h of diagnosis. In this paper, we review a rigorous, novel approach for evaluating an implementation toolkit to support adoption and effective implementation of RCE. We fielded and evaluated an RCE implementation toolkit at two clinic sites over an 8-month period. We evaluated the toolkit by assessing implementation processes, contexts, and outcomes at each clinic site, and by surveying and interviewing key implementation staff (n = 9) to solicit their feedback on the toolkit routinely throughout program implementation. This study offers preliminary evidence that the toolkit can support effective implementation of RCE and bolsters evidence regarding the impact of RCE on linkage to care. Both clinics used the toolkit to implement the RCE program with a high degree of fidelity—clients received 85–100% of intended RCE services at the clinic sites. Moreover, as a result of implementing RCE, one site saw an improvement in linkage to care from 68% at baseline to 77% during the implementation period. Staff reported that toolkit components were well-designed for communicating key information but needed to be more succinct and easier to navigate to increase their utility for busy clinic staff. We refined the toolkit to incorporate key lessons learned from our evaluation. Toolkits, especially those that have been tested with program implementers and are informed by evidence regarding implementation and client outcomes, are a critical tool for supporting the integration of evidence-based practices into routine healthcare.